Predictors and Significance of Readmission after Esophagogastric Surgery: A Nationwide Analysis - Richard PT Evans, MBBS, FRCS; Sivesh K Kamarajah, MBChB, MRCS; Felicity Evison, MSc; Xiaoxu Zou, PhD; Ben Coupland, MSci; Ewen A Griffiths, MD, FRCS (Annals of Surgery Open)
Objective:. The aim of this study is to identify risk factors for readmission after elective esophagogastric cancer surgery and characterize the impact of readmission on long-term survival. The study will also identify whether the location of readmission to either the hospital that performed the primary surgery (index hospital) or another institution (nonindex hospital) has an impact on postoperative mortality. Background:. Over the past decade, the center-volume relationship has driven the centralization of major cancer surgery, which has led to improvements in perioperative mortality. However, the impact of readmission, especially to nonindex centers, on long-term mortality remains unclear. Methods:. This was a national population-based cohort study using Hospital Episode Statistics of adult patients undergoing esophagectomy and gastrectomy in England between January 2008 and December 2019. Results:. This study included 27,592 patients, of which overall readmission rates were 25.1% (index 15.3% and nonindex 9.8%). The primary cause of readmission to an index hospital was surgical in 45.2% and 23.7% in nonindex readmissions. Patients with no readmissions had significantly longer survival than those with readmissions (median: 4.5 vs 3.8 years; P < 0.001). Patients readmitted to their index hospital had significantly improved survival as compared to nonindex readmissions (median: 3.3 vs 4.7 years; P < 0.001). Minimally invasive surgery and surgery performed in high-volume centers had improved 90-day mortality (odds ratio, 0.75; P < 0.001; odds ratio, 0.60; P < 0.001). Conclusion:. Patients requiring readmission to the hospital after surgery have an increased risk of mortality, which is worsened by readmission to a nonindex institution. Patients requiring readmission to the hospital should be assessed and admitted, if required, to their index institution.